Cardiovascular disease and chimeric antigen receptor cellular therapy - Rao, Anjali; Stewart, Andrew; Eljalby, Mahmoud; Ramakrishnan, Praveen; Anderson, Larry D.; Awan, Farrukh T.; Chandra, Alvin; Vallabhaneni, Srilakshmi; Zhang, Kathleen; Zaha, Vlad G. (Frontiers in Cardiovascular Medicine, 2022)
Chimeric antigen receptor T-cell (CAR T) therapy is a revolutionary personalized therapy that has significantly impacted the treatment of patients with hematologic malignancies refractory to other therapies. Cytokine release syndrome (CRS) is a major side effect of CAR T therapy that can occur in 70-90% of patients, with roughly 40% of patients at grade 2 or higher. CRS can cause an intense inflammatory state leading to cardiovascular complications, including troponin elevation, arrhythmias, hemodynamic instability, and depressed left ventricular systolic function. There are currently no standardized guidelines for the management of cardiovascular complications due to CAR T therapy, but systematic practice patterns are emerging. In this review, we contextualize the history and indications of CAR T cell therapy, side effects related to this treatment, strategies to optimize the cardiovascular health prior to CAR T and the management of cardiovascular complications related to CRS. We analyze the existing data and discuss potential future approaches.